2022
DOI: 10.3390/rs14153795
|View full text |Cite
|
Sign up to set email alerts
|

A Study of a Severe Spring Dust Event in 2021 over East Asia with WRF-Chem and Multiple Platforms of Observations

Abstract: In this study, we investigate the most severe East Asian dust storm in the past decade that occurred on 14–16 March 2021 based on the Weather Research and Forecasting model coupled with chemistry (WRF-Chem) and a variety of site measurements and satellite retrievals. The dust emissions from the Gobi Desert, especially over Mongolia on March 14, are the dominant sources of this intense dust event. The maximal hourly accumulated dust emissions over Mongolian and Chinese areas reached 1490.18 kt at 07:00 UTC on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…For example, between 6 and 24 May (during the early stage of this investigation), three dust storms in Central Asia seriously affected the eastern coastal provinces of China, although no data are available in the sea (China Meteorological Administration, 2022). Tang et al (2022) showed that the center of the spring dust storm reached the northwest Pacific at latitudes between 30°and 40°, which was south of our study area. The atmospheric deposition of nutrients, especially Fe, might be the main factor for the high phytoplankton biomass (i.e., Chl a) in the southern region of the study area (Figure S1).…”
Section: Influence Of Environmental Factors On the Spatial Distributi...mentioning
confidence: 85%
“…For example, between 6 and 24 May (during the early stage of this investigation), three dust storms in Central Asia seriously affected the eastern coastal provinces of China, although no data are available in the sea (China Meteorological Administration, 2022). Tang et al (2022) showed that the center of the spring dust storm reached the northwest Pacific at latitudes between 30°and 40°, which was south of our study area. The atmospheric deposition of nutrients, especially Fe, might be the main factor for the high phytoplankton biomass (i.e., Chl a) in the southern region of the study area (Figure S1).…”
Section: Influence Of Environmental Factors On the Spatial Distributi...mentioning
confidence: 85%
“…Detailed studies of the lower atmospheric conditions using various observation methods have been performed to understand the formation and transmission mechanism of dust storms [2][3][4]. The impacts of dust storm (DS) events on the physical and chemical processes show that the particles in the DS could affect the chemical reaction and energy balance in the boundary layer, further causing harm to the environment and ecosystem [5,6]. Researchers also identified key factors that contribute to the occurrence and severity of DS, such as climate change, land use change, and anthropogenic activities [7,8].…”
Section: Introductionmentioning
confidence: 99%